Constraints to Uranus' great collision IV : The origin of Prospero - Parisi, Mirta Gabriela (2008)
Context: It is widely accepted that the large obliquity of Uranus is the result of a great tangential collision (GC) with an Earth size proto-planet at the end of the accretion process. The impulse imparted by the GC affected the Uranian satellite system. Nine irregular satellites (irregulars) have been discovered around Uranus. Their orbital and physical properties, in particular those of the irregular Prospero, set constraints on the GC scenario. Aims: We attempt to set constraints on the GC scenario as the cause of Uranus' obliquity as well as on the mechanisms able to generate the Uranian irregulars. Methods: Different capture mechanisms for irregulars operate at different stages on the giant planet formation process. The mechanisms able to capture before and after the GC the Uranian irregulars are analysed. Assuming that they were captured before the GC, we calculate the orbital transfer of the nine irregulars by the impulse imparted by the GC. If their orbital transfer is dynamically implausible, they should have originated after the GC. We then investigate and discuss the dissipative mechanisms able to operate later. Results: Very few transfers exist for five of the irregulars, which makes their existence unlikely before the GC. In particular Prospero could not exist at the time of the GC. Different capture mechanisms for Prospero after the GC are investigated. Gas drag by Uranus'envelope and pull-down capture are not plausible mechanisms. Capture of Prospero through a collisionless interaction seems to be difficult. The GC itself provides a mechanism of permanent capture. However, the capture of Prospero by the GC is a low probability event. Catastrophic collisions could be a possible mechanism for the birth of Prospero and the other irregulars after the GC. Orbital and physical clusterings would then be expected. Conclusions: Either Prospero originated after the GC or the GC did not occur. In the former case, the mechanism for the origin of Prospero after the GC remains an open question. An observing program able to look for dynamical and physical families is needed. In the latter case, another theory to account for Uranus' obliquity and the formation of the Uranian regular satellites on the equatorial plane of the planet would be needed.